^muzicode$: composing and performing musical codes - Greenhalgh, Chris; Benford, Steve; Hazzard, Adrian (2016)
We present muzicodes, an approach to incorporating machine-readable ‘codes’ into music that allows the performer and/or composer to flexibly define what constitutes a code, and to perform around it. These codes can then act as triggers, for example to control an accompaniment or visuals during a performance. The codes can form an integral part of the music (composition and/or performance), and may be more or less obviously present. This creates a rich space of playful interaction with a system that recognises and responds to the codes. Our proof of concept implementation works with audio or MIDI as input. Muzicodes are represented textually and regular expressions are used to flexibly define them. We present two contrasting demonstration applications and summarise the findings from two workshops with potential users which highlight opportunities and challenges, especially in relation to specifying and matching codes and playing and performing with the system.